(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Damage of activity of the photosynthetic apparatus of a bean (Phaselus vulgaris) is investigated at positive (+50°C) and negative (-10°C) temperatures before and after influence of ammonia. It is established, that under specified condition the content of chlorophylls a and b decrease. Also their ratio (Chi a/Chi b) is broken. Change of sequence of influence of physical and chemical factors in activity of a pigment-protein complex of thylakoid membranes of the photosynthetic apparatus is differently reflected.